Site-specific climatic signals in stable isotope records from Swedish pine forests - Esper, Jan; Holzkämper, Steffen; Keppler, Frank (Trees, 2018)
Key messagePinus sylvestris tree-ring δ13C and δ18O records from locally moist sites in central and northern Sweden contain consistently stronger climate signals than their dry site counterparts.AbstractWe produced twentieth century stable isotope data from Pinus sylvestris trees near lakeshores and inland sites in northern Sweden (near Kiruna) and central Sweden (near Stockholm) to evaluate the influence of changing microsite conditions on the climate sensitivity of tree-ring δ13C and δ18O. The data reveal a latitudinal trend towards lower C and O isotope values near the Arctic tree line (− 0.8‰ for δ13C and − 2.4‰ for δ18O relative to central Sweden) reflecting widely recognized atmospheric changes. At the microsite scale, δ13C decreases from the dry inland to the moist lakeshore sites (− 0.7‰ in Kiruna and − 1.2‰ in Stockholm), evidence of the importance of groundwater access to this proxy. While all isotope records from northern and central Sweden correlate significantly against temperature, precipitation, cloud cover and/or drought data, climate signals in the records from moist microsites are consistently stronger, which emphasizes the importance of site selection when producing stable isotope chronologies. Overall strongest correlations are found with summer temperature, except for δ18O from Stockholm correlating best with instrumental drought indices. These findings are complemented by significant positive correlations with temperature-sensitive ring width data in Kiruna, and inverse (or absent) correlations with precipitation-sensitive ring width data in Stockholm. A conclusive differentiation between leading and co-varying forcings is challenging based on only the calibration against often defective instrumental climate data, and would require an improved understanding of the physiological processes that control isotope fractionation at varying microsites and joined application of forward modelling.
Gesehen am 05.09.2019